Global consultation on balancing livestock environment and human needs - Li Pun, H.H.; Mwendera, E.J.; Mares, V.; Hart, B.; Steinfeld, H.; Peden, Donald G.; Seré Rabé, Carlos; Haan, Cees de (International Agricultural Centre, 1998)
ILRI (International Livestock Research Institute) together with IDRC, World Bank and FAO were requested to organize and conduct a global electronic conference and face to face consultations which would address the issue of finding a balance between the positive roles of livestock in human affairs and their beneficial impact and the negative consequences for the local and global environment. The objective of the consultation was to give all stakeholders the opportunity to have their views on livestock, environment, and human needs interactions included in a position paper to be developed at a global meeting; based on all stakeholders' perspectives, to identify strategies (policy, research extension etc.) to alleviate the negative and enhance the positive impacts of livestock on natural resources in different types of livestock production systems in different countries and ecoregions; and to identify areas of common interests which can lead to future research and Development collaboration among institutions, based on ecoregional partnership and global networks. This paper discusses the mechanisms of this global consultation, outlines participants in the electronic conference, looks into the non-electronic local consultations, and presents conclusions and recommendations.